The effect of repeated sprints on immunological modulation and the role of fat-free mass, biological maturation and dietary inflammatory index in male athletes: a quasi-experimental study with insights for training loads control - de Almeida-Neto, P. F.; Fernandes, E. A. D.; de Assis, G. G.; Suzuki, K.; da Costa, R. F.; Atanásio, L. d. M.; Pinto, V. C. M.; Aidar, F. J.; Cabral, B. G. d. A. T.; Dantas, P. M. S. (Frontiers in Sports and Active Living, 2025)
Background: Repeated sprint exercise (RSE) induces inflammation, which may be modulated by fat-free mass (FFM), biological maturation (BM), and dietary patterns, assessed by the Dietary Inflammatory Index (DII).